Match Activity Profiles And Maximum Sprint Speed By Position During The 2023 Fifa U-17 World Cup - Abdelkarim, Debbah; belkheir, Hachi; Aziz, Nail Kessal (Journal of Sport Science Technology and Physical Activities, 2025)
The Object of the study aims to analyze and compare activity profiles and maximum sprint speed among playing position in youth elite football, for this purpose, we studied total distance covered, distances covered in all speed zones, high-speed runs, sprints, and maximum speed. On a sample composed of 240 U-17 players (884 match observation) taking part of all matches of 2023 FIFA U-17 World cup, and data were obtained through the FIFA Training Centre platform, where this platform presents post match summary reports for all games of the tournament. After collecting the results and having treated them statistically, we conclude Statistically significant differences (p < 0.001) were found across all variables. On this basis, the study recommended to implement Position-Specific Training Programs, Integrate maximum speed development in youth training, monitor and adjust match loads by Position and use activity profile data in talent identification.